Bourdieu at the bedside: briefing parents in a pediatric hospital. Issue 4 (28th January 2014) - LeGrow, Karen; Hodnett, Ellen; Stremler, Robyn; McKeever, Patricia; Cohen, Eyal
Abstract : The philosophy of family‐centered care (FCC) promotes partnerships between families and staff to plan, deliver, and evaluate services for children and has been officially adopted by a majority of pediatric hospitals throughout North America. However, studies indicated that many parents have continued to be dissatisfied with their decision‐making roles in their child's care. This is particularly salient for parents of children with chronic ongoing complex health problems. These children are dependent upon medical technology and require frequent hospitalizations during which parents must contribute to difficult decisions regarding their child's care. Given this clinical issue, an alternative theoretical perspective was explored to redress this problem. Pierre Bourdieu's theoretical concepts of field, capital, and habitus were used to analyze the hierarchical relationships in pediatric acute care hospitals and to design a briefing intervention aimed at improving parents' satisfaction with decision making in that health care setting.